(untitled) (Italian Review of Legal History, 2020)
Acceleration in modern life requires acceleration, including acceleration on the highway. The accumulation of interests that are centralized on this highway creates a conflict of interest that ends in material loss or loss of life. Many road users do not realize that the legal consequences of negligence are categorized as criminal acts because they cause others to suffer. Legal politics the issuance of Law Number 22 of 2009 concerning Road Traffic and Transportation as an embodiment of criminal policy to provide legal protection and legal certainty for citizens who are casualties of road traffic accidents. Through criminal policy, it is expected that there will be order, smoothness, security in road traffic and legal certainty and legal protection for road users.